Ecology of Flora and Fauna in Maninjau Lake - Rona Almos; Sonezza Ladyanna; Pramono Pramono (JURNAL ARBITRER, 2018)
The Maninjau Lake have been poised several times which caused by the waste of commercial aquaculture feed. The situation resulted in a drastic reduction of several members of the ecosystem in the lake. The reduction of species in an ecosystem will result in the loss of the lexicon related to the species. The current research studies the lexicon of flora and fauna in Lake Maninjau, West Sumatra Province, Indonesia in the context of ecolingusitis. The output of the current study is to provide documentation lexicon which have potential to be extinct due to ecological cases such as natural disasters and human intervention around the Lake Maninjau ecosystem. The data were collected by using observational method and interviews, then the data were analyzed using translational and referential identity method. The flora found in the waters are enceng gondok, lumuik, jaiia amun, sikajuik lauik, and Â pandan lauik. Fauna found include ideh, kijing, pensi, rinyuak, bada, gariang, nila, majalaya, kolai, lele, patin, udang, lintah, bujang sambilan, asang, rutiang, langkitang, sipuik, lokan, and acek. Some types of fauna such as rinyuak are difficult to find because they polluted by tubo. Pollution as an enemy of the ecosystem caused by human greedy behavior is one of the major factors of the language extinction.